Analisa Pengaruh Kecepatan Putar Motor DC Terhadap Jarak Lontaran Pelet Pada Mesin Pelontar Pakan Ikan - Arief Adimas Prayoga; Ah. Sulhan Fauzi (P3M Politeknik Negeri Cilacap, 2022)
Freshwater fish is a type of fish that is very popular with the wider community. The problem that often occurs in cultivators is the timing of feeding fish. This study introduces automatic pellet sowing with a DC motor as a pellet ejector. The method used is by identifying research variables. This research was conducted with 3 variations of DC motor rpm rotation with 2 different pellet sizes. The data obtained showed that the farthest ejection distance is 3 mm pellets with a rotational speed of 6000 rpm, while the closest ejection distance is 3 mm pellets with a rotational speed of 1000 rpm, and it is also concluded that the data findings are the estimated time to run out of 3 kg of pellets for each pellet sample with three variations of DC motor rotational speed. Pellets with the fastest time of 1.90 s are pellets with a size of 3 mm with a rotational speed of 6000 rpm, while the longest time is 5.2 s, namely pellets with a size of 1 mm with a rotational speed of 1000 rpm.